Consumer Loyalty Based on Service Quality and Customer Satisfaction - Dini, Fitriara Rahma; Junianto, Mahmud; Nugraha, Yoga Aji; Napitupulu, Rizal Afif A; Putri, Miranda; Anggraini, Nadiem (Universitas Dinamika, 2025)
Companies and customers can build strong relationships through customer loyalty, which serves as the main foundation in creating long-term, mutually beneficial relationships. The purpose of this study is to analyze the influence of service quality and customer trust on loyalty. Analyze the influence of service quality, trust, and customer satisfaction on customer loyalty. Analyze the influence of service quality and customer trust through satisfaction on customer loyalty. This study uses a quantitative approach with the research location at PT Pegadaian UPC Palembang Square with a population of 559 people. Furthermore, the research sample was determined to be 85 customers selected using a purposive sampling technique. Research data collection was carried out using a questionnaire. The collected data will be analyzed using multiple regression analysis techniques. The findings in this study are that (i) service quality can positively and significantly influence consumer loyalty, (ii) satisfaction can positively and significantly influence consumer loyalty, (iii) together service quality and satisfaction can positively and significantly influence consumer loyalty. This study aims to provide information and considerations for industrial businesses regarding how to increase consumer loyalty.